INSTITUSI SOSIAL: PERANNYA DALAM KEBERLANGSUNGAN RUANG PUBLIK TERPADU RAMAH ANAK DI JAKARTA - Mei Ling, Loa (Universitas Tarumanagara, 2019)
The existence of public space has become an inseparable part in the development of city residents. Humans as social creatures need a place where they can gather and interact with each other. Especially in big cities, such as Jakarta, the density that occurs makes the lack of land that can be used as public space. This certainly creates difficulties for the community to find qualified social institutions to meet their needs. It is the Child Friendly Integrated Public Space (RPTRA), an alternative run by the government to get around the function of parks and abandoned areas in Jakarta. The revival of public spaces in the midst of the community is expected to be able to accommodate the needs of citizens while at the same time strengthening community relations between city residents. The thesis used as a reference for evaluation took two locations, namely the Alfa Dahlia RPTRA located in the Tegal Alur area, West Jakarta and the RPTRA Kelapa Nias III in the Kelapa Gading area, North Jakarta. Armed with the basis of this thesis research, it will be understood further how social institutions take part in the success of the RPTRA, as well as exploring the depth of the process of institutionalizing the relationship between each supporting community and the RPTRA. This research was conducted using a qualitative approach. Data is collected and reviewed through field observations, interviews, and documentation. The findings of the study explain that the institutional process plays an important role in the sustainability of the RPTRA in the future. AbstrakKeberadaan ruang publik telah menjadi bagian yang tak terpisahkan dalam perkembangan warga kota. Manusia sebagai makhluk sosial memerlukan tempat dimana mereka dapat berkumpul dan berinteraksi satu sama lain. Khususnya di kota besar, seperti Jakarta, kepadatan yang terjadi membuat kurangnya lahan yang dapat digunakan sebagai ruang publik. Hal ini tentu menimbulkan kesulitan tersendiri bagi masyarakat untuk menemukan wadah sosial yang mumpuni untuk memenuhi kebutuhannya. Ialah Ruang Publik Terpadu Ramah Anak (RPTRA), sebuah alternatif yang dijalankan oleh pemerintah utk menyiasati fungsi taman maupun area yang terbengkalai di Jakarta. Dihidupkannya kembali ruang-ruang publik di tengah masyarakat diharapkan dapat mengakomodasi kebutuhan warga sekaligus menguatkan hubungan kemasyarakatan antar warga kota. Tesis yang digunakan sebagai acuan evaluasi mengambil dua lokasi, yaitu RPTRA Alur Dahlia yang berada di area Tegal Alur, Jakarta Barat dan RPTRA Kelapa Nias III yang berada di area Kelapa Gading, Jakarta Utara. Berbekal dasar penelitian tesis ini, akan dipahami lebih lanjut bagaimana institusi sosial mengambil peranan dalam keberhasilan RPTRA, serta mengekplorasi kedalaman proses pelembagaan hubungan antara masing-masing komunitas pendukung dan RPTRA. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif. Data dikumpulkan dan dikaji melalui observasi lapangan, wawancara, serta dokumentasi. Hasil temuan penelitian menjelaskan bahwa proses institusional memegang peranan penting dalam keberlangsungan RPTRA di masa depan.